Konsep Ketuhanan dalam Tafsir Surah Al-Fatihah: Perspektif Tarekat Al-Jam’iyatul Arifin - Hafiz Khotibul Umam; Siti Ardianti (Aksioreligia, 2026)
Surah Al-Fatihah is one of the most fundamental chapters in the Qur’an because it contains the basic principles of divinity, monotheism, and the relationship between human beings and Allah. This study aims to analyze the concept of divinity in Surah Al-Fatihah through an interpretive approach from the perspective of Tarekat Al-Jam’iyatul Arifin. This research employed a qualitative method with a field research design. Data were collected through in-depth interviews, observation, and documentation involving the mursyid and members of Tarekat Al-Jam’iyatul Arifin in Punggulan Village, Air Joman District, Asahan Regency, North Sumatra, and were supported by the study of the Qur’an and relevant tafsir literature. The results show that the concept of divinity in Surah Al-Fatihah is understood not only at the level of sharia, but also at the levels of tarekat, hakikat, and ma’rifat. In this perspective, Al-Fatihah is interpreted as a spiritual dialogue between the servant and God, as well as a representation of the existential journey of human beings toward a deeper knowledge of Allah. Thus, the integration of tafsir and Sufism produces a more comprehensive understanding of divinity that includes theological, spiritual, and practical dimensions in religious life.